1998
DOI: 10.1098/rspb.1998.0359
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Bufo marinus from its natural and introduced ranges

Abstract: The marine toad, Bufo marinus, has a broad natural distribution extending from the south-west of the USA to southern Peru and the central Amazon. It was introduced to several localities in the Caribbean and Paci¢c Oceans to control sugar cane pests. We sequenced 468 bp of mitochondrial DNA (mtDNA) containing the ND3 gene, and £anking tRNA genes from toads spanning the broad natural and introduced ranges. Consistent with the known history of introductions and expected e¡ects of serial bottlenecks, mtDNA within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
1
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 41 publications
(42 reference statements)
9
95
1
4
Order By: Relevance
“…Anopheles albimanus data suggest that a single barrier exists within Central America, which may be the mountain range that crosses Costa Rica and Western Panama (Molina-Cruz et al, 2004). The phylogeographic break between Central American plus NW Colombia and South American A. darlingi is consistent with studies of other Neotropical taxa, such as Neotropical butterflies (Brower 1994), toads (Slade and Moritz, 1998), bats (Hoffmann and Baker, 2003) and trees (Dick et al, 2003). However, Manguin et al (1999) observed substantial gene flow among populations of A. darlingi throughout its geographic range using four nonmitochondrial markers (isozyme, RAPD-PCR, ITS2, and morphology).…”
Section: Discussionsupporting
confidence: 67%
“…Anopheles albimanus data suggest that a single barrier exists within Central America, which may be the mountain range that crosses Costa Rica and Western Panama (Molina-Cruz et al, 2004). The phylogeographic break between Central American plus NW Colombia and South American A. darlingi is consistent with studies of other Neotropical taxa, such as Neotropical butterflies (Brower 1994), toads (Slade and Moritz, 1998), bats (Hoffmann and Baker, 2003) and trees (Dick et al, 2003). However, Manguin et al (1999) observed substantial gene flow among populations of A. darlingi throughout its geographic range using four nonmitochondrial markers (isozyme, RAPD-PCR, ITS2, and morphology).…”
Section: Discussionsupporting
confidence: 67%
“…A similar situation was recently hypothesized to exist regarding the cane toad, Bufo marinus. Where a pest organism exists in its natural range as two or more distinct populations, control organisms may be potentially more effective if selected from population clusters other than the one from which the pest has dispersed (Slade and Moritz, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the history of cane toads in their native habitats and their natural biological control should help decision-makers limit their impacts across their invasive range. Slade & Moritz (1998) investigated the rangewide phylogeography (from both native and introduced locations) of cane toads using 468 bp of mitochondrial DNA, confirming that introduced populations in Australia and Hawaii are most closely related to the toads from the eastern parts of Venezuela and French Guiana. They also discovered a high degree of divergence between populations on the east and west sides of the Andes.…”
Section: Methods and Their Application To Amphibiansmentioning
confidence: 99%